Calidad de agua de consumo humano en el proceso de captación, tratamiento, distribución y consumo en los sectores la Coromoto y La Ercilia de la parroquia Velasco Ibarra del cantón El Empalme, provincia del Guayas - Vera Guevara, Rosa Isabel (2015)
His research aims to evaluate by physical, chemical and microbiological quality of drinking water provided by the GAD Municipal Canton El Empalme citizens analysis. The study was conducted at the treatment plant EMAPAL EP-E and the well's Ercilia in the process of collection, treatment and consumption sectors Coromoto, Valdiviezo Gomez, Juan Montalvo, San Marcos Sanchez Gonzalez Arias Olivo and La Ercilia a total of 37 points monitored. Diagnosis of the current state of the drinking water and groundwater through an interview with the Head of potable water and surveys were conducted to determine the degree of perception of the people about water quality in the canton. Ministerial Agreement 028, WHO, EPA, INEN 1108, further statistical analysis was applied multivariate including principal component analysis, factor analysis and analysis: comparison with the results of physical-chemical and microbiological standards of quality analysis was conducted cluster shows the most significant and total parameters temperature, color, turbidity, iron, fecal coliforms. The application of quality indicators for underground capture GWQI indicates inadequate quality for drinking, NSF, Dinius and ICAUCA to surface intakes and other phases of the system, it reveals contaminated Dinius quality at the end of treatment varies acceptable quality. In the NSF storage between good and medium quality, and slightly contaminated Dinius acceptable quality, and ICAUCA good quality for all points except Juan Montalvo monitored item 5 acceptable quality. In the consumption phase NSF reveals that all sectors present between good and medium quality, Dinius establishes acceptable quality except González Sánchez The Ercilia point 11 and point 15 slightly polluted and ICAUCA provides good quality for all monitored points, and sets GWQI quality excellent except in the sector Sánchez González point 9 good quality. Manual of Good Environmental Practices for domestic storage and material internal distribution of water suitable for human consumption according to the needs required which highlights was proposed to minimize unnecessary or wasteful consumption in domestic activities specifically in the laundry.